2005
DOI: 10.1590/s1678-77572005000400003
|View full text |Cite
|
Sign up to set email alerts
|

Interexaminer agreement in caries radiographic diagnosis by conventional and digital radiographs

Abstract: The purpose of this research was to compare two digital storage phosphor systems and conventional film, as well as verify the interexaminer agreement in radiographic diagnosis on occlusal and proximal cavities. Two digital systems and conventional radiographic film were used to evaluate 144 tooth surfaces with and without cavities; the radiographs were analyzed and scored in a scale of 4 points. Thirteen undergraduates and an oral radiologist participated as examiners. A light microscopy analysis was accomplis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 12 publications
2
7
0
2
Order By: Relevance
“…Other authors had reported higher values of sensitivity but similar specificity values when BW radiographs were evaluated for occlusal caries detection [26, 27]. Looking at the correlation coefficients found in our study (Table 2) it can be observed that BW had the weakest correlation compared to all other methods and to the gold standard, respectively.…”
Section: Discussionsupporting
confidence: 76%
“…Other authors had reported higher values of sensitivity but similar specificity values when BW radiographs were evaluated for occlusal caries detection [26, 27]. Looking at the correlation coefficients found in our study (Table 2) it can be observed that BW had the weakest correlation compared to all other methods and to the gold standard, respectively.…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies showed that digital radiographs had similar diagnostic accuracy to that of conventional radiographs in the detection of caries [9,13,14]. In addition, the interobserver agreement was similar between conventional and digital radiographs [13]. In the present study, although the same X-ray source was used to obtain the conventional and digital radiographs, the exposure time for the digital radiographs was less than the exposure time for the conventional radiographs.…”
Section: Discussionsupporting
confidence: 56%
“…A previous study found great variation among examiners in the radiographic diagnosis of occlusal cavities [13]. In the present study, although the examiners were from different specialties, they had similar levels of experience.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations